2018
DOI: 10.1007/s12639-018-1062-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of Eimeria species of poultry in Kwara State, North-Central Nigeria

Abstract: Coccidiosis is one of the biggest challenges faced by the global poultry industry as the protozoan is found anywhere poultry are reared. Before now, there have been no documents on the intensity and diversity of Eimeria species of poultry in Kwara State. This study aimed to determine the prevalence and intensity of Eimeria species and its species diversity among poultry in Kwara Central, North-Central Nigeria. Five hundred and two fecal samples (from four hundred and seventy two chickens and thirty turkeys) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…In addition, the risk factors associated with Eimeria spp. included origin, sex, and extensive breeding system, consistent with the previous studies [30,31]. The prevalence of STEs was 35.3% in the feces of all the studied cattle, consistent with the studies from Mantaro Valley (Junín Region, southern Peru), which showed 30% positivity, and Indonesia (35.7%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the risk factors associated with Eimeria spp. included origin, sex, and extensive breeding system, consistent with the previous studies [30,31]. The prevalence of STEs was 35.3% in the feces of all the studied cattle, consistent with the studies from Mantaro Valley (Junín Region, southern Peru), which showed 30% positivity, and Indonesia (35.7%).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the risk factors associated with Eimeria spp. included origin, sex, and extensive breeding system, consistent with the previous studies [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…Finally, adult protozoans formed in cattle can be contaminated by oocysts, which can also infect pastures and water where protozoa will grow to sporulate. 50 Overcrowding, adult and calf cohabitation, poor farm management, lack of sanitation, and untreated cattle are all contributing factors to the high prevalence of protozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous exposure to coccidia has been found to promote development of partial immunity, thus resulting in elimination of oocysts in smaller amounts (Bangoura & Bardsley, 2020). Development of clinical signs depends on several factors, such as immunosuppression, stress, exposure to high doses of sporulated oocysts and concomitant diseases (Worku et al, 2019;Ola-Fadunsin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies in which species infecting cattle were identified have been conducted (Lopez-Osorio et al, 2020;Macedo et al, 2020;Ola-Fadunsin et al, 2020). However, in some regions where cattle-rearing is a significant activity, these data are absent.…”
Section: Introductionmentioning
confidence: 99%